Recent methods for image-based modeling and rendering - Burschka, D.; Hager, G.D.; Dodds, Z.; Jagersand, M.; Cobzas, D.; Yerex, K. (IEEE Virtual Reality, 2003. Proceedings, 2003)
A long-standing goal in image-based modeling and rendering is to capture a scene from camera images and construct a sufficient model to allow photo-realistic rendering of new views. With the confluence of computer graphics and vision, the combination of research on recovering geometric structure from un-calibrated cameras with modeling and rendering has yielded numerous new methods. Yet, many challenging issues remain to be addressed before a sufficiently general and robust system could be built to (for instance) allow an average user to model their home and garden from camcorder video. This tutorial aims to give researchers and students in computer graphics a working knowledge of relevant theory and techniques covering the steps from real-time vision for tracking and the capture of scene geometry and appearance, to the efficient representation and real-time rendering of image-based models. It also includes hands-on demos of real-time visual tracking, modeling and rendering systems.